Environmental certifications: Are they reaching the consumers? - Lara, M.; Marques, C.; Santos, M-C. (5th Annual Global Management Conference, 2013)
Information asymmetry between companies and consumers are falling, due to the digital globalization and accessibility of data. In consequence, to achieve sustainable competitive advantages in the global market, companies must pursue environment friendly practices. We observe that a rising number of companies have obtained environmental certifications of their management systems, such as ISO 14001. Although ethical concerns are shared on both the supply and demand sides, companies’ green practices may not be visible and understood by the consumers. Environmental certifications are usually included in all the company’s communication, to raise awareness in all stakeholders. This study examines the consumers’ awareness of the certification symbols of the biggest Portuguese hypermarket chains. Results show that although consumers consider very important to distinguish the difference between the symbols, they do not associate them to the right certification. Therefore, we confirm that companies are losing communication opportunities because the certification symbols do not provide immediate and clear information. The study provides suggestions that allow companies to enhance the certification communication, giving more confidence and a deeper explanation to the consumers.